Integrasi Literasi Digital dan Kecerdasan Buatan sebagai Sumber Belajar bagi Siswa SMA (Indo-MathEdu Intellectuals Journal, 2025)
The rapid development of digital technology has brought significant changes to the field of education, particularly through the use of artificial intelligence (AI) as a learning resource. In the context of 21st-century education, digital literacy skills have become essential competencies that learners must possess in order to adapt to and utilize technology critically, ethically, and productively. This article aims to conceptually examine the relationship between digital literacy and the use of AI in learning at the senior high school level. The study employs a library research method by drawing on various data sources, including national and international journal articles, scholarly books, and relevant research reports. Data collection techniques involve documentation and systematic literature review, while data analysis is conducted using content analysis to identify patterns, concepts, and theoretical findings. The results indicate that digital literacy plays a central role in determining the extent to which AI can be effectively utilized as a learning medium. Students with strong digital literacy skills tend to be able to use AI to expand their knowledge, enhance critical thinking abilities, and foster learning independence, whereas low digital literacy may lead to technological dependence and weaken reflective capacity. Therefore, strengthening digital literacy grounded in ethics and responsibility is an urgent need in optimizing the use of AI in the educational field.